Pulse transit time as a surrogate measure of changes in systolic arterial pressure in children during sleep. (8th March 2014) - Vlahandonis, Anna; Biggs, Sarah N.; Nixon, Gillian M.; Davey, Margot J.; Walter, Lisa M.; Horne, Rosemary S. C.
Summary Pulse transit time has been proposed as a surrogate measure of systolic arterial pressure, as it is dependent upon arterial stiffness. Past research has shown that pulse transit time has a significant inverse relationship to systolic arterial pressure in adults; however, studies in children are limited. This study aimed to explore the relationship between systolic arterial pressure and pulse transit time in children during sleep. Twenty‐five children (13.1 ± 1.6 years, 48% male) underwent overnight polysomnography (PSG) with a simultaneous recording of continuous systolic arterial pressure and photoplethysmography. Pulse transit time was calculated as the time delay between the R‐wave peak of the electrocardiogram (ECG) to the 50% point of the upstroke of the corresponding photoplethysmography waveform; 500 beats of simultaneous systolic arterial pressure and pulse transit time were analysed in each sleep stage for each child. Pulse transit time was normalized to each subject's mean wake pulse transit time. The ability of pulse transit time to predict systolic arterial pressure change was determined by linear mixed‐effects modelling. Significant negative correlations between pulse transit time and systolic arterial pressure were found for individual children for each sleep stage [mean correlations for cohort: non‐rapid eye movement (NREM) sleep 1 and 2 r = −0.57, slow wave sleep (SWS) r = −0.76, REM r = −0.65, P < 0.01 for all]. Linear mixed‐model analysis demonstrated that changes in pulse transit time were a significant predictor of changes in systolic arterial pressure for each sleep stage (P < 0.001). The model of pulse transit time‐predicted systolic arterial pressure closely tracked actual systolic arterial pressure changes over time. This study demonstrated that pulse transit time was accurate in tracking systolic arterial pressure changes over time. Thus, the use of pulse transit time as a surrogate measure of changes in systolic arterial pressure in children is a valid, non‐invasive and inexpensive method with many potential applications.